Growth, development and maturation of the purple (Passiflora edulis, Sims.) the whole fruit - Lederman, Ildo Elizer; Gazit, Shmuel (Pesquisa Agropecuaria Brasileira, 1993)
The growth rate pattern of purple passion fruit was studied in the southern part of the coastal plain of Israel. It has a very rapid sigmoid growth pattern and the attainment of its final size takes place in about three weeks - The relative fruitlet growth rate reaches a high outstanding peak of 210% per day, 4-7 days after fruit set. Passion fruits do not increase their dimensions after the short period of very fast growth. They keep their size and weight almost unchanged for more than two months, until they attain full ripening and abscission (aprox. 85 days after anthesis).